Answer:
0.01234567901
Step-by-step explanation:
pls make me brainliest
Simplify the expression:
7 - 5x - (3 + 5x)
Operate the parentheses. Each term changes its signs because the minus sign represents a -1:
7 - 5x - (3 + 5x) = 7 - 5x - 3 - 5x
Collect like terms:
7 - 5x - (3 + 5x) = 7 - 3 -5x - 5x
Simplify:
7 - 5x - (3 + 5x) = 4 - 10x
Answer: 4 - 10x
If you follow the steps of PEMDAS it should be Multiply by 3,subtract 2.
Answer: 19º
Step-by-step explanation:
Use sine
![Sin=\frac{opposite}{hypothenuse}](https://tex.z-dn.net/?f=Sin%3D%5Cfrac%7Bopposite%7D%7Bhypothenuse%7D)
![sin=\frac{2}{6}\\ sin=0.333\\sin^-^1=19](https://tex.z-dn.net/?f=sin%3D%5Cfrac%7B2%7D%7B6%7D%5C%5C%20sin%3D0.333%5C%5Csin%5E-%5E1%3D19)